2013
DOI: 10.1093/humrep/det078
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences with tailored use of a combined oral contraceptive: a qualitative study

Abstract: what is known already: While many studies have investigated views toward extended use of COCPs, little research has examined women's actual experiences with these regimens. study design, size, duration: This was a semi-structured qualitative interview study that was part of a larger randomized trial of a standard (21 daily pills followed by a 7-day pill-free interval) versus a tailored regimen (daily pills until 3-consecutive-day bleeding triggers a 3-day pill-free interval) of Microgynon 30w mcg (Ethinyl estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Seventy-one included studies assessed women’s discontinuation, dissatisfaction, or non-use of contraception due to experience or perception of CIMBCs (Additional file 1 ) [ 43 – 50 , 52 – 54 , 72 , 74 132 ]. Most pertained to a specific contraceptive method (implants: 20, IUDs: 12, combined OCPs: 10, progestin-only and combined injectables: 4, vaginal ring: 2), while 13 addressed multiple methods and 10 were not method-specific.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy-one included studies assessed women’s discontinuation, dissatisfaction, or non-use of contraception due to experience or perception of CIMBCs (Additional file 1 ) [ 43 – 50 , 52 – 54 , 72 , 74 132 ]. Most pertained to a specific contraceptive method (implants: 20, IUDs: 12, combined OCPs: 10, progestin-only and combined injectables: 4, vaginal ring: 2), while 13 addressed multiple methods and 10 were not method-specific.…”
Section: Resultsmentioning
confidence: 99%
“…Most pertained to a specific contraceptive method (implants: 20, IUDs: 12, combined OCPs: 10, progestin-only and combined injectables: 4, vaginal ring: 2), while 13 addressed multiple methods and 10 were not method-specific. While bleeding changes may have been inconsistently defined (by researchers and study participants) across studies, spotting, unpredictable, frequent or irregular bleeding were defined as negative side effects in 42 studies [ 43 , 48 50 , 52 – 54 , 72 , 75 , 77 , 78 , 81 , 82 , 84 , 86 , 88 92 , 94 , 97 , 98 , 100 , 102 , 105 , 106 , 108 111 , 116 – 119 , 122 , 123 , 127 – 129 , 132 ], 22 studies noted that heavy or prolonged bleeding were poorly tolerated [ 49 , 53 , 54 , 77 , 83 , 84 , 91 , 92 , 98 , 101 , 103 , 104 , 106 , 110 , 111 , 113 115 , 123 , 129 , 131 ], and 22 studies found contraceptive-induced amenorrhea to be problematic [ 44 , 48 50 , 76 , 78 , 79 , 84 , 86 , 90 , …”
Section: Resultsmentioning
confidence: 99%
“…A recent RCT of standard versus tailored COC use revealed no significant difference in continuation or satisfaction rates at 1 year between the two regimens 30. While a significant minority of women expressed a preference for regular menstrual periods in the recruitment phase, a qualitative sub-study noted high satisfaction with the reduced bleeding and relief over the medical sanctioning of extended pill use on the one hand, but a dislike of the unpredictability of bleeding and the worry that amenorrhoea might imply pregnancy on the other 88. Another recent RCT of the use of EE/DRSP in a flexible extended regimen noted a reduced number of days of bleeding/spotting and fewer withdrawal bleed episodes over 1 year in comparison with a traditional 28-day regimen of the same COC 89.…”
Section: Resultsmentioning
confidence: 95%
“…A second limitation could be that we did not ask current COC users which way they were taking the pill at their initial visit. Also, the number of patients who had changed the way they were taking their COC some weeks later at follow-up may be reflective of the HCPs not warning patients they may need more time to adjust to tailored COC use if they chose this way of pill taking 14. We did not attempt to collect demographic information, such as age, parity or educational attainment.…”
Section: Discussionmentioning
confidence: 99%